Genetic Analysis Using Partial Sequencing of Melanocortin 4 Receptor (MC4R) Gene in Bligon Goat - Latifah Latifah; D. A. Priyadi; D. Maharani; Kustantinah Kustantinah; T. Hartatik (Faculty of Animal Science, Bogor Agricultural University, 2017)
Melanocortin 4 Receptor gene is involved in sympathetic nerve activity, adrenal and thyroid functions, and media for leptin in regulating energy balance and homeostasis. The aim of this research was to perform genetic analysis of MC4R gene sequences from Bligon goats. Fourty blood samples of Bligon does were used for DNA extraction. The primers were designed after alignment of 12 DNA sequences of MC4R gene from goat, sheep, and cattle. The primers were constructed on the Capra hircus MC4R gene sequence from GenBank (accession No. NM_001285591). Two DNA polymorphisms of MC4R were revealed in exon region (g.998 A/G and g.1079 C/T). The SNP g.998 A/G was a non-synonymous polymorphism i.e., changing of amino acid from methionine (Met) to isoleucine (Ile). The SNP g.1079 C/T was a synonymous polymorphism. Restriction enzyme mapping on Bligon goat MC4R gene revealed three restriction enzymes (RsaI (GT’AC), Acc651 (G’GTAC_C), and KpnI (G_GTAC’C), which can recognize the SNP at g.1079 C/T. The restriction enzymes may be used for genotyping of the gene target using PCR-RFLP method in the future research.